Challenges relating to comparison of flavonoid glycosides dissolution profiles from Sutherlandia frutescens products - Mbamalu Oluchi N.; Syce James; Samsodien Halima (Acta Pharmaceutica)
Unlike the case of conventional drug formulations, dissolution tests have hitherto not been required for herbal medicinal products commercially available in South Africa. This study investigated dissolution of the South African Sutherlandia frutescens using selected flavonoid glycosides as marker compounds. Dissolution of markers was assessed in three dissolution media at pH 1.2, 4.5 and 6.8, and samples were analysed using a validated HPLC method. The dissolution profile of each marker varied for the different materials investigated. All three media utilised showed differences in flavonoid glycoside dissolution between the S. frutescens products evaluated, with f2 values < 50 for comparison of flavonoid dissolution from any two of the materials. Dissolution of S. frutescens materials could thus be characterised using the markers in all the media tested. This tool may be employed in the future for comparison of orally administered S. frutescens products, provided between- batch variability is evaluated and found less than between-sample variability.